Impact of Global Warming on Animal and Human Health - Patra, Biswanath (International Journal of Bio-resource and Stress Management, 2010)
Global warming has emerged as a toughest challenge to human civilization to survive with climate change which varies latitudinally and regionally involving direct and indirect relationship in increasing temperature, humidity along with spreading, intensification, and invasion of vector-borne diseases. High altitude regions are especially influenced by the global climate change which are prone to altered associations and dynamics for complex host-pathogen assemblages and emergence of zoonotic diseases with fatal effects on ecosystem structure. The potential for considerable ecological perturbation has been recognized very well but few recent empirical observations have emanated from systems across the globe. Coincidental with decades of warming, and anomalies of high temperature and humidity, the mosquito-borne diseases are now associated with emerging epidemic diseases resulting in substantial morbidity and mortality. Another contributory effect of methane production from wild and domestic ruminants is a major concern in industrialized modern animal agricultural practices, so recent advances in reducing this greenhouse gas have a great impact in the present context.